A Large-Scale Survey of Barriers and Attractors to Mental Healthcare Utilization for Active-Duty Service Members in the U.S. Department of the Air Force - J. Mark Eddy; Richard E. Heyman; Amy M. Smith Slep; Michael F. Lorber; Shu Xu; Kerry N. Makin-Byrd; Rachel E. Foster (Psychology International)
Despite expanded mental health services and outreach within the military, most active-duty members who endorse mental health problems do not seek services. Little is known about why this is the case, but cognitions may play a key role. In this study, cognitions relevant to service seeking were compared among three subgroups of active-duty members: those who endorse one or more mental health problems and sought services, those who endorse problems and do not seek services, and those who do not endorse problems. To examine differences and similarities among these groups, a stratified random sample of 162,340 was drawn from all active-duty members of the U.S. Department of the Air Force serving at 91 installations around the world. Each selected member was invited to anonymously complete the Air Force Community Assessment, and 63,227 members (39% of those invited) participated. Of these, one in five reported at least one mental health problem, and one in three reported receiving services within the past two years. Participants reporting problems and who had not sought services perceived more peer and institutional stigma, reported more knowledge and logistic barriers, reported more negative attitudes towards mental health services, and reported fewer attractors to mental health services compared with those who did not report problems. Those who reported problems and sought services reported more problems and more negative attitudes than those reporting problems who had not sought services. Nine of ten who reported problems but had not received services indicated they had no intention to seek them.